2020
DOI: 10.1371/journal.pone.0239114
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial biopsy results according to diffuse interstitial lung disease classification. Cryobiopsy versus forceps: MULTICRIO study

Abstract: Background In recent years, transbronchial cryobiopsy (TBCB) has come to be increasingly used in interventional pulmonology units as it obtains larger and better-quality samples than conventional transbronchial lung biopsy (TBLB) with forceps. No multicenter studies have been performed, however, that analyse and compare TBCB and TBLB safety and yield according to the interstitial lung disease (ILD) classification. Objectives We compared the diagnostic yield and safety of TBCB with cryoprobe sampling versus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…However, there was also some reported higher incidence of complications of approximately 5% [14] . For some type of procedure such as cryobiopsy, only the incidence of hemorrhage could reach 42.1% [15,16] . Nearly all of these studies concluded that bronchoscopy is well tolerated, but the speci c incidence of complications of different operations has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was also some reported higher incidence of complications of approximately 5% [14] . For some type of procedure such as cryobiopsy, only the incidence of hemorrhage could reach 42.1% [15,16] . Nearly all of these studies concluded that bronchoscopy is well tolerated, but the speci c incidence of complications of different operations has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…One reason may be the relatively high percentage of COP which rarely causes marked pulmonary dysfunction. Another might be selection bias; in high-risk patients with severe hypoxia and respiratory failure, we usually do not perform biopsy [ 43 ] but rely mainly on serological and radiological findings to initiate treatment as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were (1) underlying unexplained ARDS based on Berlin de nition with clinical and radiological interpretation, (2) current high resolution computed tomography (HR-CT) of the lung, (3) exclusion of an persistent or predominant infectious ARDS cause based on previous investigation including bronchioalveolar lavage (BAL), (4) multidisciplinary discussion claimed for additional tissue sampling to understand the cause and prognosis of the individual patients' ARDS, (5) individual informed consent to the TBCB given by legal representatives and (6) no severe additional condition that does not allow the performance of TBCB.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue based diagnosis was described as helpful when performed by open lung biopsy but with relevant amount of side effects [2]. Bronchoscopic tissue collection by forceps biopsy in interstitial lung disease (ILD) is reported to have only a small diagnostic yield [3]. Therefore, other methods need to be investigated.…”
Section: Introductionmentioning
confidence: 99%